Antibiotic prescribing in general practice-the rhythm of the week: a cross-sectional study - Kühlein, Thomas; Szecsenyi, Joachim; Gutscher, Andreas; Laux, Gunter (The journal of antimicrobial chemotherapy, 2010)
Overprescribing of antibiotics in primary care is a worldwide phenomenon. Prescriptions can be used to reduce the uncertainty inherent in general practice. We assumed a heightened prescribing rate on Fridays because of more uncertainty before the pending weekend.Cross-sectional study from a general practice research database with 102140 patients of 32 practices in Germany. Prescribing rates of antibiotics on different days of the week were analysed. In order to evaluate the influence of the weekday within a multivariate setting, we used SAS PROC GENMOD. This procedure was parameterized accordingly to account for the cluster design of the study.The prescribing rate of antibiotics on Fridays was 23.3% higher than the average of the other days of the working week (6.04% versus 4.90%, P<0.0001). The significance of this finding was confirmed by the multivariate analysis.There is periodic fluctuation of antibiotic prescribing rates over the week. This cannot be explained by morbidity itself. Factors beyond biomedical indication are well known to influence prescribing patterns. These factors should not only be further explored, but also acknowledged when trying to reduce overprescribing.
Gesehen am 07.03.2023